Kondisi Optimum Biosorpsi Sisik Ikan Kakap Merah (Lutjanus argentimaculatus) Terhadap Zat Warna Rhodamin B - Fransina, Eirene; Latupeirissa, Jolantje (Indonesian Journal of Chemical Research, 2016)
The research of rhodamine B dye biosorption by Red Snapper’s scale (Lutjanus argentimaculatus) powder has been done. The red snapper’s scales were cleansed with aquades and dried. The dried red snapper’s scales were grinded and sieved to powder with a 100 mesh sieve. The powder of red snapper’s scale was dried at 100 °C in oven for an hour. The biosorption process toward rhodamine B dye and its results were examined with UV-Vis spectrophotometer. The optimum condition of red snapper’s scale powder for 1.0 g of absorbent has biosorption capacity in amount of 92.740%; the optimum contact time is 120 minutes with biosorption capacity in amount of 97.264%; for 50 ppm biosorption concentration has biosorption capacity in amount of 95.598% and the optimum pH of 3 has biosorption capacity of 97.930%.